Салтово-маяцкий горизонт поселения у с. Давыдо-Никольское - Красильникова, Л.И.; Красильников, К.И. (Археологічні дослідження в Україні, 2009)
The buildings discovered in Saltovo-Majak horizon at Davydo-Mykilske settlement, according to their construction and purpose, are divided into deep pillar-supported dugout dwellings and cob wireframe husbandry buildings. The ceramics is represented mostly by large pots, at a lesser extent by kitchenware, and by some burnished tableware and amphorae. Small cattle predominate in osteology.